Studies on Human Diversity. An Attempt of a New Methodical Proposal - Piontek, Janusz; Kaczmarek, Maria (Anthropological Review, 1981)
The problem of human diversity in time and space has engaged the interest of many anthropologists, and nowadays it is still interesting, especially due to the difficulties in interpreting relations between human groups. In such a situation, the present paper constitutes a contribution to the discussion on methods of studying human group diversity and the processes of the origin, development, and breakdown of human groups (ethnogenesis). This paper is divided into three main chapters. In the first one, a general outline of the methods hitherto used in studies on ethnogenesis is recalled. The typological conception of race is briefly characterized [Czekanowski 1930, 1948, 1962; Bielicki 1961, 1962; Wierciński 1962], as well as the population one [Mayr 1974; Garlick 1978] and the biocultural one [Wierciński 1978; Strzałko et al. 1975, 1978, 1980]. In this latter one, the role of cultural factors in the variability of human groups is stressed. This fact was many times proved but not unequivocally [Hiernaux 1956; Politzer 1958; Hanna 1962; McHenry, Giles 1971; Friedlander et al. 1971; Parsons 1973; Spuhler 1972; Saltzano et al. 1977; El-Najjar 1978]. Agreement or disagreement of biological and cultural ranges of information is difficult for interpretation, especially that human groups are not easily distinguishable units and generally, they are defined on the base of certain discriminants that indicate adoption of a positivistic notion of culture. The situation when any biological diversity does not correspond with cultural one, as well as ethnogenetic processes, is difficult to interpretation. Thus, the authors present their own opinion on processes of human groups diversity, emphasizing that biological differentiation of human groups takes place in two mutually exclusive ways: either they lead to disintegration of ethnocultural systems and the emergence of "descendant ethnoses" or to integration of ethnocultural systems by means of adjustments between their cultural and biological information, as shown in figure 1. Since the authors have found these two processes responsible for changes of human groups, they are of the opinion that the correct interpretation of biological relations among groups is only possible when the character of processes in ethnocultural systems may be estimated (e.g., either disintegration or integration) and the role of biological and cultural factors that triggered off and realized given alternative processes can be described. Similar opinions were presented in previous authors papers [Piontek, Kaczmarek 1980; Czerniak, Piontek 1980; Piontek 1981]. Theoretically, the third situation may be discussed when a stationary model of the ethnocultural system is realized, however, its interpretation is not disputable, and so it is not considered here. In the second chapter, the authors discuss the problem of the so-called biological distance—a measure that has been used, regardless of methodological conceptions of human race, for the description and interpretation of human variability. The notion of it given by Czekanowski [1909] and Constandse-Westerman [1972] is mentioned here, especially for expressing the authors attitude towards this procedure. Authors, in contrast to some other anthropologists [Cain, Harrison 1958; Karve, Malhotra 1968; Malyutov et al. 1972], state that biological distance should be treated only as statistical information on human variability. The interpretation of this measure must be referred to modeling and systemic formulas based on theoretical knowledge. Such a statement is found important since ethnogenetic investigations in European groups have been based on comparative studies [Rossing, Schwidetzky 1975]. In the third chapter, for supporting the previously given point of view, three examples of three different situations are given: when the defined territory is inhabited by a poliethnic society of high cultural development, when different territories are inhabited by groups belonging to the same ethnocultural system, when large cultural differentiation of following groups is observed but at the same time, they are biologically similar to each other. The material presented as the first example is taken from Bozic’s article [1979]. Penrose’s distances among contemporary ethnic groups from Vojvodina, Yugoslavia are insignificant (table 1). It means that criteria for distinguishing ethnic groups may not allow ordering of biological variability. The examined population is mendelian one with high intragroup variability (the coefficient of variation is rather high and do not differ considerably among groups) although culturally it may be divided into several subgroups. However lack of biological differences among them is understandable when adaptive character of culture is taken into account for distinguishing groups (e.g. the level of socio-economical development). The second example presents biological distances between Middle Ages Slavic groups from Europe [Rössing and Shwidetzky 1975] expressed in terms of Penrose's distances. Differences between various groups are often significant. Since all presented here human series belong to one common ethnic group the interpretation of this result is difficult. (table 2). The third situation presents comparative data for human groups from Neolithic and Early Bronze periods from certain territories of Central Europe [Bach 1972, Wierciński 1973] (table 3). Penrose's distances computed for these groups are insignificant except for representatives of Bell Beaker Culture. Detailed characteristic of all these archaeological cultures [Hensel, Tabaczyński 1978:136, 139] supports an expectation about so-called “continuous” model of cultural changes between groups and biological difference between Bell Beaker Culture and other is also archeologically prooved [Wiślański 1978]. Three situations referenced here illustrate authors” opinion on the methodology in studies on human groups genesis. As it was stressed adaptive character of culture and detailed description of both biological and cultural factors responsible for human diversity must be adopted in ethnic studies. In final remarks authors emphasized the need for further modelling and systemic formulas in ethnogenesis as well as detailed methodological and methodical directions of description, classification and interpretation of biocultural information with specially stressed definitions of supra-time variables describing cultural changes in human groups.